Conformational flexibility at the substrate binding site in the lactose permease of Escherichia coli - Weinglass, Adam B. (The National Academy of Sciences, 1999)
Glu-126 (helix IV) and Arg-144 (helix V) are charge paired and play a critical role in substrate binding in the lactose permease of Escherichia coli. When Glu-126 is replaced with Asp, the permease has relatively high activity, implying that helix V has sufficient flexibility to allow Arg-144 to accommodate the decreased length of the carboxylate-containing side chain of Asp-126. Helices IV and V contain five Gly residues at positions 115, 121, 141, 147, and 150, all of which are conserved in the oligosaccharide/H(+) symport family of the major facilitator superfamily. To test the notion that these residues may contribute to conformational flexibility, each residue was replaced with Ala in either the wild type or the Glu-126 → Asp mutant. Although the replacements are well tolerated in the wild type, the mutations severely inactivate substrate binding and transport in the Glu-126 → Asp background, with the exception of Gly-121 → Ala, which retains significant activity. Strikingly, moreover, in two instances (Gly-150 → Ala and Gly-141 → Ala), significant activity is recovered when Ala residues at approximately parallel positions in helix IV (Ala-122 or Ala-127, respectively) are replaced with Gly. In addition to providing further evidence that the major determinants for substrate binding in the permease are at the interface between helices IV and V, the findings indicate that the region is conformationally flexible.